2007
DOI: 10.1097/acm.0b013e318159d070
|View full text |Cite
|
Sign up to set email alerts
|

Preparing the Personal Physician for Practice: Changing Family Medicine Residency Training to Enable New Model Practice

Abstract: After two years of intensive study, in 2004 the Future of Family Medicine report concluded that the current U.S. health care system is inadequate and unsustainable, and called for changes within the specialty of family medicine to ensure the future health of the American public. With guidance and encouragement from many disciplines and health experts, a set of 10 recommendations was established to accomplish a transformative change in how family physicians serve their patients and how the essential function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 25 publications
0
51
0
Order By: Relevance
“…A report from the Pacific Northwest found that only 5% of family medicine faculty had cesarean delivery privileges. 14 Recent experiments in family medicine residency education-the P4 project 24,25 and the Accreditation Council for Graduate Medical Education Length of Training Pilot 26 -may shed more light on the connection between educational approaches and the provision of advanced maternity care services by graduates of these programs. Cesarean deliveries may be a particularly important component of extended training options; previous research has found a correlation between training in this procedure and its provision in rural practice.…”
Section: Discussionmentioning
confidence: 99%
“…A report from the Pacific Northwest found that only 5% of family medicine faculty had cesarean delivery privileges. 14 Recent experiments in family medicine residency education-the P4 project 24,25 and the Accreditation Council for Graduate Medical Education Length of Training Pilot 26 -may shed more light on the connection between educational approaches and the provision of advanced maternity care services by graduates of these programs. Cesarean deliveries may be a particularly important component of extended training options; previous research has found a correlation between training in this procedure and its provision in rural practice.…”
Section: Discussionmentioning
confidence: 99%
“…3,60 In this endeavor, we can profit from the experiences of internal medicine and family medicine, because both fields are going through a similar methodology to achieve improvements in their residency training programs. [61][62][63][64][65] It is our hope that creative approaches fostered under this process will enhance learning, improve patient and family outcomes, and lead to more efficient, effective pediatric care.…”
mentioning
confidence: 99%
“…[13][14][15] The National Demonstration Project, launched by the American Academy of Family Physicians in 2006 in an effort to assess the comprehensive PCMH model and findings related to transformation process requirements, reported in 2010 that this evolution was a complex process requiring motivated and engaged practice members. Over time, this process should continue to emphasize core attributes of collaborative care within primary care and attention to mental and public health.…”
Section: Facilitators and Early Adoptersmentioning
confidence: 99%